Bentuk Sikap Bahasa Pengguna Sosial Media terhadap Pemertahanan Bahasa Indonesia - Nurma Alfinda W, Nurma Alfinda W (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2021)
Social media has become a communication tool to connect people who do not know each other in a place or platform such as Instagram, Facebook, Line, TikTok, Twitter, WhatsApp and others. Social media is one of the reasons for the creativity of the social media user community in creating new languages ​​which ultimately lead to language attitudes. This study aims to describe the form of language attitudes of social media users towards the defense of Indonesian with a qualitative descriptive research method using online questionnaires. The results of the study include Garvin and Mathiot's three language attitudes, namely language loyalty, language pride and awareness of the existence of norms.